2019
DOI: 10.20527/jwem.v7i2.210
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change on Agriculture for Local Paddy Water Requirement Irrigation Barito Kuala, South Kalimantan, Indonesia

Abstract: Increasing rice consumption demand in Indonesia has provided serious problems such as food insecurity. Being the major staple food, rice production is the main priority of medium and long term development planning in Indonesia. Local rice production is strongly affected by climate conditions, especially in South Kalimantan. Nowadays, the world must adjust to climate change. One of significant effects of changing climate on agriculture is related to productivity. Evapotranspiration is the major cause of loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The impact of climate change on irrigation water demand for local rice cultivation was 56% and 25%, higher than current conditions in July, September, and October, respectively (Achyadi et al, 2019). Climate change also has a significant impact on fluctuations in agricultural production and food security.…”
Section: Bibliometric Coupling Of Abstractmentioning
confidence: 94%
“…The impact of climate change on irrigation water demand for local rice cultivation was 56% and 25%, higher than current conditions in July, September, and October, respectively (Achyadi et al, 2019). Climate change also has a significant impact on fluctuations in agricultural production and food security.…”
Section: Bibliometric Coupling Of Abstractmentioning
confidence: 94%
“…Yuliawan and Handoko (2016) [ 132 ] utilized the Shierary Rice model to evaluate the impact of temperature rise on rice crop yield in Indonesia, revealing a reduction in yield of up to 11.1% and 14.4% in rainfed and irrigated areas, respectively, for a 1 °C temperature increase. Achyadi et al (2019) [ 155 ] analyzed water requirements for irrigation units in Barito Kuala, South Kalimantan, under climate change scenarios, concerning local rice cultivation. The study revealed that the impact of climate change on water irrigation requirements for local paddy cultivation during the 2050s and 2090s would be 56% and 25% higher than current conditions in July and September–October, respectively.…”
Section: Challenges and Opportunities Of Modelling Approaches In Indo...mentioning
confidence: 99%
“…The monthly average temperature in South Kalimantan is 26,22°C; the minimum temperature mainly occurs in January and December. The maximum temperature occurs in May [13]. Planting patterns using superior rice can be done up to 2 times a year, but the recommended planting period is the beginning of the first planting period, November-February, and the second planting period, March-June.…”
Section: Study Areamentioning
confidence: 99%